Frequency modulation in EEG signals - Vijayakumar, V.; Yusoff, Rahimi; Eswaranr, C. (2006)
In this paper we first explain how EEG signals can be described using Lommel functions. When the Lommel functions are allowed to time-evolve and analysed using the method of instantaneous frequency, we obtain a frequency modulated harmonic spectrum. This perspective allows new insights in interpreting the nonlinear behavior of EEG signals such as chaos.